Establishment of a physical exercise evaluation index system for school-age children with asthma - Yueheng Zhao; Xianmei Meng; Suqing Wang (PLoS ONE, 2025)
Objective To construct a comprehensive physical exercise evaluation index system for asthmatic children aged 6–12 years. Design Based on knowledge-attitude-practice(KAP) theory, we constructed an item pool for a physical exercise evaluation index system using a literature review and semistructured interviews and refined the index system through two questionnaire cycles with Delphi experts. Results For the two questionnaire rounds, the recovery rate was 100%, the experts’ authority coefficients were 0.850 and 0.836, and the coordinated coefficients were 0.167 and 0.202 (P<0.001). Finally, four first-level indicators, namely, disease factors, exercise environment, exercise practice, and exercise psychology; 11 second-level indicators; and 50 third-level indicators were developed as a physical exercise evaluation index system for asthmatic children. Conclusion A physical exercise evaluation index system built using a literature review, qualitative interviews, and Delphi technique can provide scientific guidance for children with asthma, caregivers and health professionals to comprehensively assess the children’s physical exercise.